Safety stock optimization under lead time ambiguity - Chong Keun Kim; Pan Soo Kim; Joon Yeop Kwon (Global Business & Finance Review (GBFR), 2022)
Purpose: The purpose of this study is to investigate how ambiguity faced by the risk-neutral manager affects the firm's optimal level of safety stock. Design/methodology/approach: This study adopts the traditional model of Arrow et al. (1951) and employ a manager who has multiple prior beliefs about the probability distribution of the lead time. Findings: This study finds that facing lead time ambiguity, the manager becomes more conservative when choosing the optimal stock level to hold and the amount of safety stock. Research limitations/implications: The future research would consider a risk-averse manager who could be compensated or punished as a result of stock management. Then the future research would examine the interactive effects of the manager's risk aversion and lead time ambiguity on the optimal safety stock level. Originality/value: This would be the first study that investigates the effects of ambiguity on the level of safety stock.
Keywords: 650; Ambiguity; safety stock; stochastic lead time